On the problem of correctness in the stark spectroscopy of high-density plasma streams - Chebotarev, V.V.; Garkusha, I.E.; Makhlaj, V.A.; Mitina, N.I.; Solyakov, D.G.; Tereshin, V.I.; Trubchaninov, S.A.; Tsarenko, A.V. (Вопросы атомной науки и техники, 2000)
This work is devoted to investigations of probable errors of the spectral methods for electron density measurements. The theoretical calculation of the optical plasma thickness τ for the hydrogen Hβ line was performed for the different values of the electron density and temperature. It was demonstrated that impact of the optical thickness on the electron density measurements is negligible small in our conditions.